Role of Mitochondria in Viral Infections - Srikanth Elesela; Nicholas W. Lukacs (Life, 2021)
Viral diseases account for an increasing proportion of deaths worldwide. Viruses maneuver host cell machinery in an attempt to subvert the intracellular environment favorable for their replication. The mitochondrial network is highly susceptible to physiological and environmental insults, including viral infections. Viruses affect mitochondrial functions and impact mitochondrial metabolism, and innate immune signaling. Resurgence of host-virus interactions in recent literature emphasizes the key role of mitochondria and host metabolism on viral life processes. Mitochondrial dysfunction leads to damage of mitochondria that generate toxic compounds, importantly mitochondrial DNA, inducing systemic toxicity, leading to damage of multiple organs in the body. Mitochondrial dynamics and mitophagy are essential for the maintenance of mitochondrial quality control and homeostasis. Therefore, metabolic antagonists may be essential to gain a better understanding of viral diseases and develop effective antiviral therapeutics. This review briefly discusses how viruses exploit mitochondrial dynamics for virus proliferation and induce associated diseases.